Examining Linkage Audit Quality Factors Intervening By Time Budget Pressure - Mohammad Aldrin Akbar; Najarudin Toatubun; Abdul Haris Mzen; Imran Syafei Muhammad Nur; Septyana Prasetianingrum (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2022)
Public accountants are independent auditors who provide services to the general public, especially in auditing financial statements made by their clients. The task of a public accountant is to examine and give an opinion on the fairness of the financial statements of a business entity based on predetermined standards. The public accounting profession is responsible for increasing the reliability of the company's financial statements. The public can obtain reliable financial statement information as a basis for decision-making. The research objective is to answer the phenomenon of the variable, namely the Effect of Auditor Competence, Audit Complexity, Auditor Independence on Audit Quality. The research method uses Multiple Regression Analysis. From the research results obtained the following results Auditor Independence has the most dominant effect on Audit Quality, Audit Complexity also has a significant but negative impact on Audit Quality. Meanwhile, Auditor Competence also significantly impacts Audit Quality.